Forging an Identity: An Insider-outsider Study of Processes Involved in the Formation of Organizational Identity - Gioia, Dennis A.; Price, Kristin N.; Hamilton, Aimee L.; Thomas, James B. (Administrative Science Quarterly, 2010)
We investigated the processes involved in forming an organizational identity, which we studied during the founding of a distinctive new college by using an interpretive, insider-outsider research approach. The emergent grounded theory model suggests that organizational identity formed via the interplay of eight notable processes, four of which occurred in more-or-less sequential, stage-like fashion —(1) articulating a vision, (2) experiencing a meanings void, (3) engaging in experiential contrasts, and (4) converging on a consensual identity—plus four recurrent processes that were associated with two or more of the sequential stages: (5) negotiating identity claims, (6) attaining optimal distinctiveness, (7) performing liminal actions, and (8) assimilating legitimizing feedback. The findings show that internal and external, as well as micro and macro influences affected the forging of an organizational identity. In addition, we found that both social construction and social actor views of identity-related processes were not only germane to the formation of organizational identity but that these processes were also mutually constitutive in creating a workable identity.